Pancreatic Laceration in a Female Collegiate Soccer Athlete: A Case Report - Powers, Michael E. (National Athletic Trainers Association, 2013)
OBJECTIVE: To characterize the diagnosis of pancreatic trauma in an athletic population and to raise awareness among health care providers of the possibility of this life- and organ-threatening injury. BACKGROUND: An 18-year-old, previously healthy female collegiate soccer athlete sustained a direct blow from an opponent's knee between the left and right upper abdominal quadrants while attempting to head the ball. She initially presented with only minimal nausea and discomfort, but this progressed to abdominal pain, tenderness, spasm, and vomiting. She was referred to the emergency department, where she was diagnosed with a pancreatic laceration. DIFFERENTIAL DIAGNOSIS: Duodenal, hepatic, or splenic contusion or laceration; hemorrhagic ovarian cyst. TREATMENT: The patient underwent a distal pancreatectomy and total splenectomy. UNIQUENESS: Pancreatic injuries, particularly those severe enough to warrant surgical intervention, are extremely rare in athletes. CONCLUSIONS: Recognition of a pancreatic injury can be very challenging outside the hospital setting. This is problematic, because a delay in diagnosis is a significant source of preventable morbidity and mortality after this rare injury. Thus, early identification depends on a high index of suspicion, a thorough examination, and close observation. It is imperative that athletic trainers and other health care professionals be able to identify this condition so that referral and management can occur without delay.